2020
DOI: 10.3390/f11020228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Vegetation on Outdoor Thermal Comfort: Comparison between a Mediterranean City (Lecce, Italy) and a Northern European City (Lahti, Finland)

Abstract: This paper is devoted to the application of the modelling approach, as one of the methods for the evaluation of thermal comfort, to neighborhoods located in two cities characterized by a different climate, i.e., a Mediterranean city in southern Italy (Lecce) and a northern European city in southern Finland (Lahti). The impact of the presence of vegetation in both places is evaluated and compared, further considering alternative scenarios for thermal comfort improvement. The thermal comfort condition is express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 54 publications
4
33
0
1
Order By: Relevance
“…From Table 3, it can be concluded that Alternative 2 is the best alternative to improve the outdoor thermal comfort for this area, as adding larger trees to the model has a large effect on the PET value. This is consistent with the studies of Gatto et al [24] and Cheung and Jim [25], which clearly show the benefits of large trees compared to other cases.…”
Section: Resultssupporting
confidence: 92%
“…From Table 3, it can be concluded that Alternative 2 is the best alternative to improve the outdoor thermal comfort for this area, as adding larger trees to the model has a large effect on the PET value. This is consistent with the studies of Gatto et al [24] and Cheung and Jim [25], which clearly show the benefits of large trees compared to other cases.…”
Section: Resultssupporting
confidence: 92%
“…ENVI-met required an ad hoc tuning of surface boundary conditions to satisfactorily predict nocturnal cooling. Gatto et al [52] applied and validated ENVI-met for the evaluation of thermal comfort in neighborhoods located in two cities characterized by a different climate, i.e., Lecce (taken as a Mediterranean city) and a northern European city in southern Finland (Lahti). Results showed that, at pedestrian height, the presence of vegetation led to an improvement of thermal comfort in the summer in both neighborhoods.…”
Section: A Brief Overview Of Recent Microclimate and Air Quality Studies In Leccementioning
confidence: 99%
“…ENVI-met was successfully employed in studies analyzing the effects of vegetation on microclimate and thermal comfort in the urban environment, where it was thoroughly described [34][35][36][37][38][39][40]; it was also employed for an investigation of air quality, focusing on air pollutant deposition and dispersion in several studies [41][42][43][44][45][46][47][48][49], which mostly found a satisfactory agreement with observations and concluded that, although it is not a very sophisticated model, it provides sufficient functions for establishing small-scale pollutant distribution for studies of urban greening in near-road environments. Specifically, the model was only applied to evaluate the microclimate in some districts of Lecce [50][51][52], while, to our knowledge, there are no papers applying the model to evaluate the impact of urban greening on the dispersion of air pollutants in the city of Lecce.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cold or cool materials with high reflectance, are often proposed as a solution to mitigate UHI effect [8]. Also green urban infrastructures make urban environments less thermally stressful improving thermal comfort: trees, green roofs, and vegetation can mitigate UHI effects by shading building surfaces, deflecting radiation from the sun, and with the evapotranspiration effect [9,10]. Greening plays a major role in mitigating the local climate, directly impacting the outdoors thermal comfort of city pedestrians, as well as reducing the energy demand of buildings.…”
Section: Introductionmentioning
confidence: 99%